Recent Advances in Acute Kidney Injury Epidemiology - SIEW, Edward D. (2012)
PURPOSE OF REVIEW: Expanding rates of acute kidney injury (AKI) coupled with increasing awareness of its short and long-term sequelae have focused efforts to identify patients at risk for developing this disease and its complications. This review details recent attempts to identify novel risk factors for AKI, describe further refinements in the diagnostic and prognostic approach to this disease using biological markers of injury, and highlights features of AKI that independently predict poor long-term outcomes. RECENT FINDINGS: The presence of proteinuria predicts the development of AKI independently of glomerular filtration rate (eGFR). Initial results from a large prospective study of AKI biomarkers in cardiac surgery indicate lower agreement with serum creatinine as an AKI standard than observed in early studies. AKI severity and duration are important predictors of chronic kidney disease (CKD) and long-term mortality. A minority of patients surviving AKI with decreased kidney function is seen by a nephrologist. SUMMARY: While the pathophysiologic link unclear, proteinuria is an easily measurable risk factor for AKI worth considering before anticipated procedures or medication exposures with nephrologic risk. Investigation extending beyond agreement with serum creatinine is needed to fully understand the diagnostic and prognostic value of AKI biomarkers. Severity and duration are components of AKI that can help risk-stratify survivors in need of monitoring or nephrology referral.